ACCURACY OF INFORMATION ON SCORPION ACCIDENTS: A STRATEGY TO COMBAT DISINFORMATION - de Azevedo Soares, Fabiana; de Faria Pereira Neto, André; Paolucci, Rodolfo Pimenta; Souza, Claudio Mauricio Vieira (Seven Editora, 2025)
New information and communication technologies have enabled unparalleled access, production, and dissemination of information. However, However, the veracity, completeness, and intelligibility of this information can be questionable. Misinformation concerning health-related topics can cause harm to individuals and communities. Assessing the quality of health information on the internet can be a critical approach to adress this issue. This article presents an instrument for evaluating the accuracy of information on scorpion accidents, a growing problem in Brazil, as revealed by the results of the evaluation of information on scorpion accidents available on the Ministry of Health’s “Health A-Z” website. The instrument consists of 21 indicators distributed in the dimensions of prevention, symptoms, diagnosis and treatment of scorpion accidents. The results indicate that 43% of the information available on the Ministry of Health’s website complies with the indicators constructed. DOI: https://doi.org/10.56238/sevened2025.028-005